The effects of mirror therapy with tasks on upper extremity function and self-care in stroke patients - Park, Youngju (J Phys Ther Sci, 2015)
[Purpose] The purpose of this study was to determine the effects of mirror therapy with tasks on upper extremity unction and self-care in stroke patients. [Subjects] Thirty participants were randomly assigned to either an experimental group (n=15) or a control group (n=15). [Methods] Subjects in the experimental group received mirror therapy with tasks, and those in the control group received a sham therapy; both therapies were administered, five times per week for six weeks. The main outcome measures were the Manual Function Test for the paralyzed upper limb and the Functional Independence Measure for self-care performance. [Results] The experimental group had more significant gains in change scores compared with the control group after the intervention. [Conclusion] We consider mirror therapy with tasks to be an effective form of intervention for upper extremity function and self-care in stroke patients.